Fabrication of miniature sunflower seeds peeler / Nur Farra Farhana Abdullah - Abdullah, Nur Farra Farhana (2022)
A sunflower peeler is one tool that is increasingly used in human life. The purpose of is peeler is to reduce time to peel the “kuaci” and to helps distinguish good seeds from bad ones. The issue constantly encountered is that removing the shells from sunflower seeds is very difficult and time-consuming. Individuals who love to eat "kuaci" and make it their everyday snack will have a problem if the peeler is not used. The hull of the sunflower seeds will not be cluttered with this peeler because it has a mini drawer. The objective of this project is to produce a "kuaci" peeler that can be taken around everywhere, also known as a miniature "kuaci" peeler. To assure the project's success, several methods use have been implemented. Among them is cutting, drilling, welding (MIG) and threading with a lathe machine. This project start with conduct a research on sunflower peelers, search literature about this project, make a market survey and from the market survey, it can find five designs that fit this project's requirements. Then, select the design from pugh chart, choose the best, and then complete the fabrication process. Simply put, this project can benefit kuaci's lover and meet the goal purpose.